2021
DOI: 10.3390/cells10123530
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 3 Protects against Restraint Stress-Induced Gastrointestinal Injury in Mice

Abstract: Psychological stress increases the risk of gastrointestinal (GI) tract diseases, which involve bidirectional communication of the GI and nerves systems. Acute stress leads to GI ulcers; however, the mechanism of the native cellular protection pathway, which safeguards tissue integrality and maintains GI homeostasis, remains to be investigated. In a mouse model of this study, restraint stress induced GI leakage, abnormal tight junction protein expression, and cell death of gut epithelial cells. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(63 citation statements)
references
References 93 publications
0
63
0
Order By: Relevance
“…P-selectin gene knockout (KO) ( Selp −/ − ) mice were employed to specify the involvement of P-selectin regulation under stress. Using the restraint stress mouse model orally fed with Evans blue dye [ 15 ], we found that Selp −/ − mice displayed higher GI leakage than the wild -type mice ( Figure 2 ), implicating the protective role of P-selectin in the GI system. Because male ( Figure 2 ) and female ( Figure S3 ) mice behaved similarly in response to the stress, this suggested that there are no sex differences in stress-induced GI leakage in mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…P-selectin gene knockout (KO) ( Selp −/ − ) mice were employed to specify the involvement of P-selectin regulation under stress. Using the restraint stress mouse model orally fed with Evans blue dye [ 15 ], we found that Selp −/ − mice displayed higher GI leakage than the wild -type mice ( Figure 2 ), implicating the protective role of P-selectin in the GI system. Because male ( Figure 2 ) and female ( Figure S3 ) mice behaved similarly in response to the stress, this suggested that there are no sex differences in stress-induced GI leakage in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Pathophysiological changes associated with anxiety and stressed behavior of experimental animals could occur after restraint stress [ 12 ]. Evans blue, a GI-nonabsorbable dye, will not normally appear in plasma when orally fed [ 15 ]. By examining the plasma levels of Evans blue, we can measure stress-induced GI leakage in real time [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To distinguish populations of platelets, NDs and platelet-ND aggregates, CellTracker Blue Dye (ThermoFisher Scientific) labeled mouse platelets, and red fluorescent 50 nm NDs (brFND-50, FND Biotech) were used in this experiment. The counts of platelet aggregates per field (> 400 pixels) and the total platelet aggregate area (pixels) per field were analyzed using ImageJ software (version 1.32; National Institutes of Health, USA) ( 38 , 68 ).…”
Section: Methodsmentioning
confidence: 99%